Antidepressant-like effect of picralima nitida total crude alkaloidal fraction in mice - Prince Dagadu Okyere; Christian Chukwuma Ndu; Donatus Wewura Adongo; Charles Kwaku Benneh; Eric Woode; Edmund Ekuadzi; Wonder Kofi Mensah Abotsi; Eric Boakye-Gyasi; Priscilla Kolibea Mante (Scientific African)
In 2019, WHO, reported that an estimate of 350 million people globally have depression. Despite the advances made in current pharmacotherapy, about 30–40 % of patients receive insufficient treatment because of the increased occurrence of partial or non-response as well as delayed onset of antidepressive action. Herbs, however, offer a vital solution to potential pharmacological agents for effective depression management. Our study investigated the potential antidepressant-like action of Picralima nitida total crude alkaloidal fraction in mice.Crude total alkaloidal extract from P. nitida (PNE) was obtained by cold macerating dried, powdered seeds in petroleum ether for 48 h, liberating total alkaloids with 6 % acetic acid, precipitating total alkaloid with concentrated ammonia, and dissolving precipitate in chloroform. The potential antidepressant-like action of PNE was studied in the Forced Swim Test (FST) and Tail suspension test (TST) in mice (n = 8), together with a study of the potential influence of noradrenergic and serotonin pathways.PNE significantly reduced immobility times in mice in the FST (F8, 42 = 15.74, P < 0.0001) and TST (F7, 46 = 22.79, P < 0.0001). Pretreatment with reserpine, a vesicular monoamine transporter inhibitor, which depletes monoamines reversed the initial reduction in immobility time of mice administered PNE in TST and FST. PNE did not significantly increase 5-HTP induced head-twitches, but it potentiated noradrenaline toxicity. PNE at 300 mg/kg resulted in 60 % probability of survival while PNE at 30 and 100 mg/kg resulted in 80 % probability of survival over 48 h Antidepressant-like effects of PNE, at all doses, were reversed by AMPT pretreatment.This study found that PNE has antidepressant-like effect, predominantly due to effects on noradrenergic neurotransmission, offering a new perspective mechanisms of its pharmacological activity. These findings highlight the plant's potential as a source for developing novel, accessible and culturally relevant antidepressant drugs particularly in regions like sub-Saharan Africa.